Representasi Tekstual terhadap Pemberitaan Festival Hak Asasi Manusia 2021 di Media Elektronik - NFN Rahmawati; Nada Fadhilah; Tiara Vidya Amalia; Khaerudin Kurniawan (Balai Bahasa Kalimantan Tengah, 2022)
This study aims to describe the differences in human rights news reporting in the iNews Pagi, Kabar Utama tvOne, and Tribunnews Update programs. This study used a qualitative descriptive method with the help of Norman Fairclough's theory of critical discourse analysis, especially the analysis of textual representation. The data were in the form of the transcription of the news